2017
DOI: 10.13189/wjcat.2017.050201
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness and Use of Electronic Learning Platforms: A Case of a Developing Country

Abstract: E-learning is seen as a potent option for mass education globally. Consequently, institutions are hastily adopting it to meet the 21 st century education demands, often without recourse to considering the antecedents that promotes the success or otherwise of this mode of instruction. In view of this, the study investigates the awareness and use of e-learning platforms in some selected senior high schools in the Accra metropolitan area of Ghana with emphasis on parameters such as perception, training, accessibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…They are also characterized by the ease of development and modernization at the lowest cost and effort (Abdul-Kader & Khalifa, 2021). The advantages of EDPs can be listed as: motivating learners to continue learning by offering them interactive and participatory activities between learners, combining social networks to help users exchange opinions and ideas, enabling the teacher to create virtual classes to conduct dialogues between users, providing a digital library containing learning resources, easing the evaluation of the learners' work by the teacher, and encouraging of communication between teachers and students from all over the world (Adzobu, 2014;Ahmed, 2016;Amandu et al, 2013;Nyagorme et al, 2017). In addition, numerous studies (e.g., Giordano & Marongiu, 2021;Liu et al, 2020;Soy-Muner, 2020;Yang et al, 2021) have emphasized the significance of EDPs in meeting the training needs of teachers and attaining training objectives.…”
Section: Theoretical Framework and Review Of Relevant Literature Trai...mentioning
confidence: 99%
“…They are also characterized by the ease of development and modernization at the lowest cost and effort (Abdul-Kader & Khalifa, 2021). The advantages of EDPs can be listed as: motivating learners to continue learning by offering them interactive and participatory activities between learners, combining social networks to help users exchange opinions and ideas, enabling the teacher to create virtual classes to conduct dialogues between users, providing a digital library containing learning resources, easing the evaluation of the learners' work by the teacher, and encouraging of communication between teachers and students from all over the world (Adzobu, 2014;Ahmed, 2016;Amandu et al, 2013;Nyagorme et al, 2017). In addition, numerous studies (e.g., Giordano & Marongiu, 2021;Liu et al, 2020;Soy-Muner, 2020;Yang et al, 2021) have emphasized the significance of EDPs in meeting the training needs of teachers and attaining training objectives.…”
Section: Theoretical Framework and Review Of Relevant Literature Trai...mentioning
confidence: 99%
“…Selfefficacy theory derived from psychology and presented a theoretical framework which accounted for human behaviour changes from diverse modes of treatment (Bandura, 1997), Darko-Adjei (2018) found that fresh DE students inadequately prepared for the Sakai LMS. In the same line of thought, most Senior High Schools (SHS) graduates got their first computer experience at the high schools' ICT laboratory, which were inadequately furnished and often manned by poorly trained ICT staff, coupled with high student-to-computer ratio, and limited timetable period for practice (Nyagorme et al, 2017). Lack of computer selfefficacy or confidence posed a significant barrier to engaging in DE (Tagoe, 2012;Lee et al, 2005;Acheampong, 2016).…”
Section: Challenges Of Distance Educationmentioning
confidence: 99%